FROM THE HISTORY OF THE DEVELOPMENT OF THE CITY OF FERGANA (LATE 19TH CENTURY - EARLY 20TH CENTURY) (Scientific journal of the Fergana State University, 2023)
The article analyzes issues such as the development of the city of Fergana after its foundation, population growth, based on archival documents, statistical data, and the literature of the studied period. Also, the improvement works carried out in the city are shown on the basis of original materials.